Analysis and design of single and dual element bowtie microstrip antenna embedded with planar long wire for 5G wireless applications. Issue 3 (4th November 2019) - Sharma, Sandeep; Mainuddin; Kanaujia, Binod K.; Khandelwal, Mukesh K.
Abstract: In this article, a low‐profile bowtie shaped planar antenna loaded with long wire is designed, analyzed, and fabricated, which is fed by microstrip line and presented with and without metallic reflector. It consists of a planar long‐wire antenna, which is designed at 27 GHz and terminated with the input impedance of a planar bowtie shaped element supported by defected ground structure. This terminating element works as a load resistance for long wire. Furthermore, two‐element antenna arrays with proposed bowtie structure is designed, analyzed, and presented. Design equations of proposed structure are presented along with the various aspects including return loss, gain, and radiation characteristics. Proposed antenna is working within the frequency band ranging from 27 to 29 GHz and may be used for 5G wireless applications as it offers high gain within the operating frequency. Simulated results are validated by measured results of fabricated prototypes.